(untitled) (Bangladesh Journal of Plant Taxonomy, 2019)
DNA barcoding and morpho-anatomical characters of two forms of Convolvulus arvensis L. growing in Asir region, Saudi Arabia were studied. We applied three molecular markers, ITS, rbcL and matK for phylogenetic reconstruction in combination with 24 morpho-anatomical characters to provide proposal for the recognition of its population under two forms. Plant samples were collected from ten various populations of C. arvensis supposed to be of two different forms, and finally these have been found to be of two new forms (small leaf) and form (large leaf) for the flora of Saudi Arabia. TWINSPAN results showed that there was negative group with twenty one objects including stem length, stem thickness, seed shapes, petiole length, leaf apex, leaf length, petal circumference, leaf width, capsule length, capsule width, stamen length, anther width, anther length, carpel length, venations type, pollen grains shape, T.S of stem, root and leaf, stigma shape and anther base surface and positive group including hairs, stomata and anther shape. Dendrogram upon morpho-anatomical characters resolved two main clusters, one cluster of form (large leaf) and the other of form (small leaf). Amplified gene region for the form (small leaf)-rbcL showed 100% identity with C. lineatus; form (small leaf)-matK and form (large leaf)-matK had 99% identity with Calystegia sepium (L.) R. Br. Form of (small leaf)–ITS had 100% identity with that of C. arvensis; form (large leaf)-rbcL had 100% identity with those of C. arvensis and C. lineatus. Form (large leaf)–ITS had 99% identity with that of C. arvensis. The results of molecular phylogenetic analyses based on certain morphological and rbcL data support two main clusters within C. arvensis which is consistent with two forms, form (small leaf) and form (large leaf).